Emerging per- and polyfluoroalkyl substances (PFAS) in human milk from Sweden and China. Issue 10 (17th September 2020) - Awad, Raed; Zhou, Yihui; Nyberg, Elisabeth; Namazkar, Shahla; Yongning, Wu; Xiao, Qianfen; Sun, Yaije; Zhu, Zhiliang; Bergman, Åke; Benskin, Jonathan P.
Abstract : Emerging per- and polyfluoroalkyl substances (PFAS) were investigated in human milk from Stockholm (Sweden), and the cities of Shanghai, Jiaxing, and Shaoxing (China). Abstract : Twenty per- and polyfluoroalkyl substances (PFAS) were determined in human milk from residents of three Chinese cities (Shanghai, Jiaxing, and Shaoxing; [ n = 10 individuals per city]), sampled between 2010 and 2016. These data were compared to a combination of new and previously reported PFAS concentrations in human milk from Stockholm, Sweden, collected in 2016 ( n = 10 individuals). Across the three Chinese cities, perfluorooctanoate (PFOA; sum isomers), 9-chlorohexadecafluoro-3-oxanone-1-sulfonic acid (9Cl-PF3ONS; also known as 6:2 Cl-PFESA or by its trade name "F53-B"), and perfluorooctane sulfonate (PFOS; sum isomers) occurred at the highest concentrations among all PFAS (up to 411, 976, and 321 pg mL −1, respectively), while in Stockholm, PFOA and PFOS were dominant (up to 89 and 72 pg mL −1, respectively). 3 H -Perfluoro-3-[(3-methoxy-propoxy)propanoic acid] (ADONA) was intermittently detected but at concentrations below the method quantification limit ( i.e. <10 pg mL −1 ) in Chinese samples, and was non-detectable in Swedish milk. The extremely high concentrations of F53-B in Chinese milk suggest that human exposure assessments focused only on legacy substances may severely underestimate overall PFAS exposure in breastfeeding infants.